KOTA CERDAS DAN KEBIJAKAN PENDIDIKAN DALAM PERSPEKTIF SOSIOLOGI - Mauluddin, Agus; Lestari, Sisca (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to show that "smart cities" are smart society. Smart cities apply the principle of meritocracy in every policy, including education policy. With the perspective of functional structure sociology as a analysis, and examining facts through literature, this study also shows that the foundations of the myth of Meritocracy and the theory of correspondence do not hold firm that social reproduction in society is obvious, but our argument, the social status of the actor is not always linear with the actor's social status. Social mobility will be realized because the principle of meritocracy is applied in every policy. As a result, meritocratic policies are the main principles of smart sociological cities (apart from system integration and application of technology in a city).